Broad-spectrum antiviral activity of the sigma-1 receptor antagonist PB28 against coronaviruses - Song, Gaojie; Cheng, Lingling; Dong, Xingpeng; Li, Dapeng; Cheng, Jia; Shang, Chao; Li, Xiao; Zhu, Ran; Zhang, Cuiling; Li, Junwei (Frontiers in Microbiology, 2025)
The continuous evolution of coronaviruses poses persistent and severe threats to both human and animal health. While α- and β-coronaviruses mainly infect mammals, including humans, γ-coronaviruses predominantly infect poultry, causing substantial economic losses. Their rapid mutation rates and wide host tropism underscore the urgent demand for pan-coronavirus therapeutics. Here, we systematically investigated the antiviral potency and mechanism of action of PB28, a selective sigma-1 receptor antagonist, across α-, β-, and γ-coronaviruses. Molecular docking predicted a stable interaction between PB28 and the sigma-1 receptor. PB28 exhibits robust in vitro antiviral activity, effectively inhibiting the replication of β-coronaviruses (SARS-CoV-2 and its Beta, Delta, and Omicron variants; HCoV-OC43), α-coronaviruses (PEDV and TGEV), and γ-coronaviruses (IBV). Broad-spectrum antiviral efficacy is further validated by viral titration assays. In vivo, PB28 administration in K18-hACE2 mice infected with SARS-CoV-2 Delta and BALB/c mice infected with HCoV-OC43 led to significantly reduced viral loads, attenuated multi-organ pathology, and improved survival and body weight maintenance. In parallel, PB28 treatment in IBV-infected chicken embryos and neonatal chicks enhanced survival, supported embryogenesis, and alleviated tissue damage. Collectively, PB28 demonstrates cross-genus antiviral efficacy, likely mediated through modulation of the sigma-1 receptor. These findings highlight PB28 as a promising lead compound for the development of pan-coronavirus therapeutics.